Early ultrasonic vocalization deficits and related thyroarytenoid muscle pathology in the transgenic TgF344-AD rat model of Alzheimer’s disease - Rudisch, Denis Michael; Krasko, Maryann N.; Barnett, David G. S.; Mueller, Kimberly D.; Russell, John A.; Connor, Nadine P.; Ciucci, Michelle R. (Frontiers in Behavioral Neuroscience, 2024)
Alzheimer's disease (AD) is a progressive neurologic disease and the most common cause of dementia. Classic pathology in AD is characterized by inflammation, abnormal presence of tau protein, and aggregation of β-amyloid that disrupt normal neuronal function and lead to cell death. Deficits in communication also occur during disease progression and significantly reduce health, well-being, and quality of life. Because clinical diagnosis occurs in the mid-stage of the disease, characterizing the prodrome and early stages in humans is currently challenging. We use the validated TgF344-AD transgenic rat model to test the central hypothesis that pathology and related behavioral deficits such as communication dysfunction manifest in the peripheral nervous system and corresponding target tissues in the early stages. The primary aims of this study are to test the hypotheses that: (1) changes in ultrasonic vocalizations (USV) occur in the prodromal stage and worsen at 9 months of age, (2) inflammation and AD-related pathology can be found in the thyroarytenoid muscle at 12 months of age, and to (3) demonstrate that the TgF344-AD rat model is an appropriate model for preclinical investigations of early AD-related vocal deficits. USVs were collected from male TgF344-AD (N = 19) and wildtype (WT) Fischer-344 rats at 6 and 9 months and acoustically analyzed for duration, mean power, principal frequency, low frequency, high frequency, peak frequency, and call type. RT-qPCR was used to assay peripheral inflammation and AD-related pathology in the TA muscle of male TgF344-AD rats (n = 6) and WT rats (n = 6) at 12 months of age. We revealed a significant reduction in mean power of USVs from 6 to 9 months of age and increased peak frequency over time in TgF344-AD rats compared to controls. Significant downregulation of AD-related genes Uqcrc2, Bace2, Serpina3n, and Igf2, as well as downregulation of pro-inflammatory gene Myd88 was found in the TA muscle of TgF344-AD rats at 12 months of age. Our findings demonstrate early and progressive vocal deficits in the TgF344-AD rat model and dysregulation of AD-pathology-related genes and inflammatory genes in the TA muscles of TgF344-AD rats in the early stage of the disease.